Informal caregivers’ perceived effectiveness of caregiver training for caregivers of index stroke survivors - Prinsloo, Marinda (My University, 2021)
Introduction: Globally, strokes are considered the third leading cause of disability, with increased caregiver requirements due to long-term disability. Additionally, a stroke not only impacts the survivor but also their family and friends. Thus, there is a need to determine the perceived effectiveness and gaps in training provided to informal caregivers. Method: A non-experimental prospective longitudinal quantitative approach with a convenience sample of 31 participants was used. Participants were interviewed through face-to-face or telephonic semi-structured interviews. A questionnaire with set parameters was administered on discharge and again at six weeks post-discharge, to determine the perceived effectiveness and gaps of caregiver training provided at a private Rehabilitation Unit in Pretoria (Rita Henn and Partners [RHP]). However it is important to note that the response rate for participation in the follow-up questionnaire was 61%. Results: The results indicated that caregivers felt prepared to care for the stroke survivor. The informal caregivers perceived the index stroke survivors (ISS) to be independent in completing their activities of daily living (ADL), therefore they perceived caregiver training to be effective. However, when it came to instrumental ADL, the caregivers’ perception of the training was either that they did not receive it or that they did not need to assist the ISS in returning to these tasks. In addition, informal caregivers perceive productive participation or return-to-work as insufficient as they still need help when assisting ISSs to return to work. Furthermore, the informal caregivers were able to identify perceived gaps in the caregiver training they received and provided suggestions for improvement. Conclusion: Informal caregivers are often new to their role and responsibilities. They require informal caregiver training to assist the ISS with the transition from in-patient rehabilitation to home reintegration. Informal caregivers of ISSs perceive caregiver training to have both positive and negative aspects related to occupational performance areas, psychosocial aspects, how the caregiver training is presented as well as the much-needed continuation of caregiver support and follow-up services. Valuable information related to the perceived gaps in caregiver training and the perceived ability of informal caregivers to care for the ISS was obtained from this research study. This could guide future clinical practice, specifically related to caregiver perceptions of training provided at the Rehabilitation Unit
A research report submitted to the Faculty of Health Science, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science in Occupational Therapy, 2021